2021
DOI: 10.5194/mr-2-489-2021
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetic resonance free ligand conformations and atomic resolution dynamics

Abstract: Abstract. Knowledge of free ligand conformational preferences (energy minima) and conformational dynamics (rotational energy barriers) of small molecules in solution can guide drug design hypotheses and help rank ideas to bias syntheses towards more active compounds. Visualization of conformational exchange dynamics around torsion angles, by replica exchange with solute tempering molecular dynamics (REST-MD), gives results in agreement with high-resolution 1H nuclear magnetic resonance (NMR) spectra and comple… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…This new polar interaction could explain the excellent LLE 36 of compound 22 compared to compound 16. By NMR free ligand conformational and atomic level dynamical analysis, 37 the pyridine ring preorganized in solution as observed in the crystal structure (Figure 3, such that the pyridine ring is co-planar to the plane of the carboxamide and the pyridinyl N is trans to the carboxamide oxygen atom, consistent with electronic repulsion). Despite this co-planar conformation, no strong intramolecular hydrogen bond was measured experimentally between the pyridine nitrogen lone pair and the carboxamide NH based on the NMR temperature coefficient, A nmr value, 38 and the absence of an NOE between the carboxamide NH and pyridinyl CH.…”
Section: ■ Results and Discussionmentioning
confidence: 82%
“…This new polar interaction could explain the excellent LLE 36 of compound 22 compared to compound 16. By NMR free ligand conformational and atomic level dynamical analysis, 37 the pyridine ring preorganized in solution as observed in the crystal structure (Figure 3, such that the pyridine ring is co-planar to the plane of the carboxamide and the pyridinyl N is trans to the carboxamide oxygen atom, consistent with electronic repulsion). Despite this co-planar conformation, no strong intramolecular hydrogen bond was measured experimentally between the pyridine nitrogen lone pair and the carboxamide NH based on the NMR temperature coefficient, A nmr value, 38 and the absence of an NOE between the carboxamide NH and pyridinyl CH.…”
Section: ■ Results and Discussionmentioning
confidence: 82%
“…NMR relies on this for the nuclei to respond to electromagnetic waves as perturbations in the presence of an external magnetic field. In addition to small organic molecules, NMR spectroscopy is a critical method to obtain high-resolution information about proteins, DNA, and RNA. , It can also be used to obtain knowledge of energy minima and barriers by observing conformational dynamics of proteins . This can be pivotal in the process of drug discovery.…”
mentioning
confidence: 99%
“…1,2 It can also be used to obtain knowledge of energy minima and barriers by observing conformational dynamics of proteins. 3 This can be pivotal in the process of drug discovery.…”
mentioning
confidence: 99%
“…To rationalize this surprising SAR and inform further designs, NMR conformational analysis was carried out to investigate the free ligand conformational preferences in solution. Examination of the torsional profile of all rotatable bonds in the system highlighted the aryl rotor as having a high rotational energy barrier with a bi-modal distribution . We observed that in both compounds 12 and 13 , the methoxy group effectively locks the aryl ring orientation such that the 2-OMe and 6-OMe point away from the six-membered ring, irrespective of the aryl ring substituent in the 3-position (Figure a).…”
Section: Resultsmentioning
confidence: 87%
“…Examination of the torsional profile of all rotatable bonds in the system highlighted the aryl rotor as having a high rotational energy barrier with a bi-modal distribution. 31 We observed that in both compounds 12 and 13, the methoxy group effectively locks the aryl ring orientation such that the 2-OMe and 6-OMe point away from the six-membered ring, irrespective of the aryl ring substituent in the 3-position (Figure 3a). As a consequence, compound 13 with 6-OMe aryl substitution is effectively preorganized into the bioactive conformation (green), whilst compound 12 is locked into a non-bioactive conformation (red).…”
Section: ■ Results and Discussionmentioning
confidence: 89%